Addressing Consumer Misconceptions on Antibiotic Use and Resistance in the Context of Sore Throat: Learnings from Social Media Listening - Sabiha Essack; John Bell; Douglas Burgoyne; Khalid Eljaaly; Wirat Tongrod; Thomas Markham; Adrian Shephard; Elsa López-Pintor (MDPI AG, 2023)
A misunderstanding of the mechanism of action and bacterial targets of antibiotics by consumers may drive inappropriate antibiotic use and antimicrobial resistance (AMR). Tackling AMR requires an in-depth understanding of consumer beliefs and misconceptions. We explored consumer conversations on a number of social media platforms on antibiotic use and AMR in the context of sore throat and how coronavirus disease 2019 (COVID-19) affected online conversations between 1 January 2018 and 25 November 2021 across eight countries. Five distinct consumer groups were identified (antibiotic-preserving peer educators, antibiotic-cautious consumers, medication-resistant antibiotic opponents, believers in the strength of antibiotics, determined pro-antibiotic consumers) with a wide spectrum of beliefs around antibiotics in sore throat. Many opinions were based upon misconceptions, the most prominent of which was that antibiotics are strong medications that can treat all types of sore throat. COVID-19 had a multifaceted effect on the sore throat and AMR conversation. Sore throat triggered anxiety as consumers feared it may be a COVID-19 symptom while engagement in conversations around antibiotics for COVID-19 increased. Finally, consumers sought multiple routes to access antibiotics, such as directly from the pharmacy or by attempting to persuade physicians to prescribe. Knowledge obtained from this study could be used to develop focused approaches to dispel consumer misconceptions and mitigate AMR.